2022
DOI: 10.3390/cancers14020434
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease and Cancer: Treatment and Prognosis Regarding Gender Differences

Abstract: Cardiovascular disease and cancer remain the leading causes of hospitalization and mortality in high-income countries. Survival after myocardial infarction has improved but there is still a difference in clinical outcome, mortality, and developing heart failure to the disadvantage of women with myocardial infarction. Most major cardiology trials and registries have excluded patients with cancer. As a result, there is only very limited information on the effects of coronary artery disease in cancer patients. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
(264 reference statements)
0
6
0
Order By: Relevance
“… 44 CAD and cancer share numerous risk factors and cancer patients carry a higher prevalence of cardiovascular risk factors than cancer-free controls. 44 The predictive value of CAD for morbidity and mortality is well documented; however, it was not previously considered in the context of elderly patient CE. Promotion of healthy aging should be primarily based on long-life prevention of cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 44 CAD and cancer share numerous risk factors and cancer patients carry a higher prevalence of cardiovascular risk factors than cancer-free controls. 44 The predictive value of CAD for morbidity and mortality is well documented; however, it was not previously considered in the context of elderly patient CE. Promotion of healthy aging should be primarily based on long-life prevention of cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43] CAD morbidity is higher in persons with cancer than in the general population. 44 CAD and cancer share numerous risk factors and cancer patients carry a higher prevalence of cardiovascular risk factors than cancer-free controls. 44 The predictive value of CAD for morbidity and mortality is well documented; however, it was not previously considered in the context of elderly patient CE.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial infarction and coronary heart disease prevalence is high in cancer [46]. The uppermost prevalence was reported during the first 6-12 months after cancer diagnosis [47][48][49], and the risk remains high even after 10 years [49]. Arterial thrombosis, along with the creation of microthrombi, usually begins when lipid plaques build up in the arterial walls, triggering the activation of platelets and inflammatory cells, as in coronary heart disease [50].…”
Section: Pathophysiology Of Vtementioning
confidence: 99%
“…Recent studies showed that hematologic diseases can be treated well with a variety of modern therapies [8], but when combined with myocardial infarction (MI), they lead to an excess mortality [9][10][11]. However, there are few retrospective studies in the literature that have specifically examined HM and CAD [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%